Peranan Badan Perpustakaan Daerah Provinsi Sumatera Barat dalam Menumbuhkan Minat Baca Anak - Rahman, Azi; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
The study aims to know the role of The Regional Library West Sumatera in growing interest in reading the children. The research is a sort research of descriptive set which was done through the process of observation went straight through the interview process to the informant in the development and management of child’s interest The Regional Library West Sumatera. The method of analisys is carried out in a descriptive. Based on the interview process has been identified that The Regional Library West Sumatera have done a number of programs to faster interest in children to reading. The library have a area for children, as well as the effort to local governments to supplement it’s reading in children. In addition the government also estabilished a rapport with school in West Sumatera in general and the city of Padang at particural times. In accordance with the open interview process, there have been identified that a major constrait facing the area on the West Sumatera is a matter of funding to complete the materials reading, especially for children. In order to develop the interest reading of The Regional Library west Sumatera to do a program that supports children’s creativity as having the painting and various other positive event.Keyword: children, reading, The Regional Library West Sumatera.